Implementation Of The Utilization Of Village Funds During The Covid-19 Pandemic - Suci, Wulan; Akbar, Faisal; Afnila, (Mahadi: Indonesia Journal of Law, 2023)
Village funds are budget allocations on-budget that can be used directly to support efforts to mitigate the impact of Covid-19 at the household and village levels. This study aims to gain a deeper understanding of the regulation of the use and utilization of village funds during the Covid-19 pandemic, the implementation of village fund usage during the Covid-19 pandemic in the Air Batu Subdistrict, and the supervision of village fund management during the Covid-19 pandemic. The results show that the utilization of village funds during the Covid-19 pandemic remains based on the provisions of Law Number 6 of 2014 concerning Villages. The use of village funds for handling Covid-19 can also be based on the Regulation of the Minister of Village Development of Disadvantaged Regions, and Transmigration of the Republic of Indonesia Number 13 of 2020 concerning the Priorities of Village Fund Utilization for the Year 2021. This regulation explicitly governs (1) National economic recovery in accordance with the authority of the village, (2) National priority programs in accordance with the authority of the village, (3) Adaptation of new village habits. The supervision of the use of village funds during the Covid-19 pandemic is carried out by the local government of the district/city (Inspectorate), sub-district head (camat), Village Consultative Body (BPD), and village communities. This is regulated in the Regulation of the Minister of Home Affairs Number 73 of 2020 concerning the Supervision of State Financial Management.